The making of the atomic bomb - Rhodes, Richard, 1937- (New York : Simon & Schuster, 1986)
Describes in human, political, and scientific detail the complete story of how the bomb was developed, from the turn-of-the-century discovery of the power of the atom, to the first bombs dropped on Japan.
Bibliography: p. 848-861.
Includes index.
Keywords: Atomic bomb -- History